(untitled) (Al-Academy, 2024)
This includes Creative Management and leadership in Museums and the administration of art exhibitions. the research problem is Encapsulated in the following main question: what is the Significance of Arts Management and artistic Entrepreneurship in the Creative Economy? the research questions derived from this include: what is the System of Arts Project Management? what is artistic Entrepreneurship for artists? what is the Concept of the Creative Economy? the research objectives are to understand the System of Arts project Management, comprehend the nature of artistic entrepreneurship for artists, and explore its role in the Creative Economy. The Theoretical framework and previous studies are Encompassed in the research, covering axes that address arts Management in General and its Entrepreneurial Role in the field of the Creative Economy. the research adopts a Descriptive research Methodology to identify the Importance of arts Management and Entrepreneurship among art students and the Economic role of their work in the job market. The research Community focuses on Significant Projects and initiatives in Visual Arts that actively participate in global and local climate and environmental issues. the research relies on a purposive (purposeful) sampling Method, Selecting four important projects as the research sample. The research results include identifying the Arts and their Management Mechanisms, Defining Entrepreneurialism and its role in Investing in the arts field. the Spotlight is also placed on the Importance of Activities, products, and services in the Visual Arts in building Economically and Socially profitable Art Projects. Research Recommendations include Promoting an Entrepreneurial Culture in the arts, Raising Awareness within the Artistic Community about the importance of proper investment in the arts according to entrepreneurial Standards, and intensifying and Diversifying Projects in the arts in General, especially in Visual Arts. Research Proposals suggest intensifying studies and research on Entrepreneurship in the arts, translating research studies that include Artistic Entrepreneurship and Successful Entrepreneurial Models in the Arts, and Garnering support from Governments and Funding Bodies for the Production of Projects in Visual Arts.